Live unnoticed =(Lathe biōsas) : on the vicissitudes of an Epicurean doctrine - Roskam, Geert. (Philosophia antiqua,, 2007)
Against the background of age-old Greek wisdom, Epicurus' advice to 'live unnoticed' (lathe biosas) was particularly provocative and scandalous. Why, after all, would an unknown Greek soldier in Agamemnon's army have been happier than famous Achilles? Or why should an ordinary Athenian be regarded as more blessed and enviable than Pericles? Yet Epicurus' ideal was far from unattractive, guaranteeing as it did a quiet and untroubled existence far from the dangerous turmoil of public life. This book casts new light on Epicurus' socio-political philosophy through a careful analysis of his arguments. It also shows how the ideal of an 'unnoticed life' was received during the later history of Epicureanism and how it occasionally occurs in ancient Latin poetry.